2016
DOI: 10.1177/0333102416651284
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent coma and fever in familial hemiplegic migraine type 2. A prospective 15-year follow-up of a large family with a novelATP1A2mutation

Abstract: Background Familial hemiplegic migraine (FHM) is a rare monogenic migraine subtype characterised by attacks associated with transient motor weakness. Clinical information is mainly based on reports of small families with only short follow-up. Here, we document a prospective 15-year follow-up of an extended family with FHM type 2. Patients and methods After diagnosing FHM in a patient with severe attacks associated with coma and fever, we identified eight more family members with FHM and one with possible FHM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…FHM-causing mutations have been identified in three genes encoding a calcium channel (FHM1), a sodium channel (FHM3) and the alpha2 subunit (FHM2) (De Fusco et al, 2003). At least 80 mutations in ATP1A2 have been described to cause FHM2 (Figure 4, reviewed in Bottger et al, 2012; Pelzer et al, 2016). In contrast to the ATP1A1 mutations that all target recurrent hotspots, many of the mutations in ATP1A2 have been reported just once, and they affect both the transmembrane and the cytoplasmic parts of the protein.…”
Section: Disease-causing Mutations In Nak-atpase Alpha Isoformsmentioning
confidence: 99%
“…FHM-causing mutations have been identified in three genes encoding a calcium channel (FHM1), a sodium channel (FHM3) and the alpha2 subunit (FHM2) (De Fusco et al, 2003). At least 80 mutations in ATP1A2 have been described to cause FHM2 (Figure 4, reviewed in Bottger et al, 2012; Pelzer et al, 2016). In contrast to the ATP1A1 mutations that all target recurrent hotspots, many of the mutations in ATP1A2 have been reported just once, and they affect both the transmembrane and the cytoplasmic parts of the protein.…”
Section: Disease-causing Mutations In Nak-atpase Alpha Isoformsmentioning
confidence: 99%
“…We present a table with the mutations described in the literature from 2003 to 2016 and their main phenotypic characteristics (Table 1). Some of the mutations produce long-lasting attacks of hemiplegic migraine, but they are related to other neurological pathologies such as seizures and mental retardation [1], coma, and fever [23]. The case we present had no other neurological diseases apart from FHM.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, the confusion, hemiplegia, hemiconvulsions, disturbances of consciousness, and extensive cytotoxic edema indicating severity of the disease are considered to be part of the same spectrum in FHM2, and CSD has been suggested as a possible underlying mechanism. 13 Furthermore, glutamate excitotoxicity can also produce secondary mitochondrial metabolic dysfunctions, and some studies about FHM2 have showed mild reduction in NAA and mild increase in lactate content in 1 H-MRS, cytotoxic edema such as an eosinophilic change of neurons, acute swelling of oligodendrocytes and astrocytes in the widespread cerebral cortex, and subcortical white matter in autopsy, suggesting some abnormalities with other metabolic diseases such as mitochondrial encephalopathy in FHM2. 14 In this case, the patient was diagnosed with severe encephalopathy of FHM2, presenting extensive cortical edema in neuroimaging, progressive symptoms, and neurological deficits, suggesting long-lasting duration of the disease.…”
Section: Discussionmentioning
confidence: 99%